ETHNOMATHEMATICS OF DAYAK TRADITIONAL CLOTHING - Setia Widia Rahayu; Hendi Santosa (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2024)
Ethnomathematics is a branch of science that studies the relationship between mathematics and cilture, including traditions, arts and social life. This research aims to reveal the mathematical concepts contained in traditional Dayak clothing, especially in their geometric motifs and patterns. The method used is a qualitative approach with ethnographic analysis of traditional clothing artifacts, interviews with traditional leaders, and literature studies. The research results show that Dayak traditional clothing contains various mathematical concepts, such as symmetry, geometric transformations (rotation, translation, reflection), and fractal patterns. Symmetry is found in the arrangement of the carved motifs, while repetition and fractal patterns can be seen in ornamental details such as the distinctive tendrils of leaves and flowers. This research shows that the cultural heritage of the Dayak tribe not only has aesthetic value, but also educational value which can be developed as contextual mathematics teaching material. It is hoped that these findings will increase understanding of the relevance of mathematics in everyday life and promote the preservation of local culture.